The Role of Poincaré Resonances in the Collapse of Quantum Waves and in the Formation of Consciousness (Global Journal of Science Frontier Research, 2023)
He comments briefly on having shown in previous works that the factors that make possible the formation of a biological consciousness would also serve for the formation of a primary universal consciousness including a hypothesis by Amit Goswami of the need for this primary consciousness in the solution of an intertwined hierarchy According to his opinion this intertwined hierarchy would appear in the collapse of quantum waves a process that is necessary for the formation of human consciousness Next he addresses the theme proposed in the title of this work which constitutes his hypothesis that the collapse of quantum waves is caused by Poincar Resonances It presents and discusses aspects that justify and result from this hypothesis showing the similarity between the behavior of these resonances and that of the synapses that occur between neurons in the human brain It also presents an attempt to resolve the impasse of the coexistence of a conscience supposedly immaterial with matter in the same realm being discarded the dualism a philosophy little accepted by the scientific community Finally he expressed his wish that the bridge that emerged between biological beings and the universe being recognized could impact people who would see that they are not separate from the world but that they are the world that they are part of the universe
Keywords: resonance; collapse; waves; consciousness